CECO wave energy converter: Experimental proof of concept - Paulo Rosa Santos (2015)
This paper presents the experimental proof of concept of CECO, an innovative wave energy converter designed to convert simultaneously the kinetic and the potential energy of ocean waves into electrical energy, based on the oblique motion of two floating modules. First, the main characteristics of CECO and its work principle are briefly presented. Then, the behavior of the device is analyzed for different wave conditions and modes of operation (power take-off damping levels and device inclinations), based on results obtained with a physical model built on a geometric scale of 1/20. CECO performance strongly depends on the incident wave characteristics, the device inclination angle, and the damping introduced by the power-take-off. Relative capture widths of up to 14% were reached in this initial study, confirming that CECO is a valid technology to extract energy from waves. The application of wavelets showed that CECO response occurs mainly in the frequency of incident waves during the entire test duration. (C) 2015 AIP Publishing LLC.